The larvae of Allogamus antennatus (McLachlan 1876), Allogamus mendax (McLachlan 1876) and Allogamus pertuli Malicky 1975 (Trichoptera: Limnephilidae) with notes on ecology and zoogeography - Waringer, Johann; Graf, Wolfram; Malicky, Hans (Zootaxa, 2012)
The paper gives a description of the hitherto unknown or poorly known larvae of Allogamus antennatus (McLachlan 1876),Allogamus mendax (McLachlan 1876) and Allogamus pertuli Malicky 1975. Information on the morphology of the larvae isgiven and the most important diagnostic features are illustrated. In the context of already available keys, the larva of A. anten-natus keys together with Annitella obscurata (McLachlan 1876) and Annitella thuringica (Ulmer 1909). The species may beseparated by the presence of setal groups between posteromedian and lateral metanotal sclerites in A. antennatus and differ-ences in head width, central prosternite proportions and lateral fringe length. Allogamus mendax keys together with Allogamusuncatus (Brauer 1857); both species are very similar except in head width. Finally, A. pertuli keys with Melampophylaxmucoreus (Hagen 1861) and M. nepos (McLachlan 1880). Whereas a setal band anterior of the lateral protuberance on the firstabdominal segment is present in A. pertuli, such a feature is lacking in the two Melampophylax species. With respect to distri-bution, A. antennatus is restricted to the southern Alps and the Appennine peninsula, A. mendax to the western Alps and A. pertuli is endemic to the Pindos region in Greece. In addition, ecological characteristics are briefly discussed.